The effects of recovery interventions following a repeated rugby union (sevens) game simulated protocol - Jones, B.; Lander, J.; Brubaker, D. (The biomedical basis of elite performance. 19-21 March 2012, London, UK. Abstracts & Manuscripts, 2012)
It has been established that rugby places extremely high physiological and psychological stresses upon players. It has also been demonstrated that the incidence of injury within rugby matches is higher than other contact sports (Gill et al 2006). Additionally recovery methods within rugby have been under-researched, especially when compared to other sports (Duthie et al 2003). The need for effective recovery interventions is essential to facilitate player revival and safety (Gill et al 2006). The purpose of this study was to compare the effectiveness of four different recovery interventions following a rugby 7`s game simulated protocol and to determine whether any, or all, of the four recovery interventions were effective. Twelve undergraduate Premiership Level Rugby Union players completed a Wingate anaerobic cycle test (WAnT), Countermovement Jump test (CMJ), the Total Quality Recovery Questionnaire (TQR) and muscle soreness diagrams. Testing sessions were separated by one week. Subject`s completed the England Anaerobic Fitness Test (E-set), then received one of four different recovery interventions; Passive recovery (PR), Active Recovery (AR), Cold Water Immersion (CWI) or Combined Recovery (COMB). 24hours later subjects repeated the pre-test assessments. A fully within groups` factorial ANOVA was used to compare results. Perceptual responses revealed that PR was perceived to provide significantly lower levels of recovery compared to AR/CWI/COMB (14.0 (1.63) vs. 15.4 (1.43), 15.4 (1.71), 15.6 (2.91)): (p < .05). Performance variables; CMJ displayed no significant differences between PR vs. AR/CWI/COMB (p > .05). WAnT analysis produced no significant difference between PR vs. AR/CWI/COMB (p > .05). This study supports previous research that CWI provides an improved perceptual response of recovery compared to PR (Roswell et al 2009). The study also supports previous studies in that no significant differences were found between PR, AR, CWI and COMB recovery protocols for performance measures (Kinugasa and Kilding 2009). The current study lends support to the majority of recovery literature presently available, and despite the popularity of CWI, active recovery and combined recovery as recovery interventions, when compared to passive recovery their use remains unsubstantiated. During competition, turnaround times between games can be very short. The recovery intervention employed must be effective. Many coaches believe that something is better than nothing, however placing a greater demand upon the athlete`s time while implementing a noneffective recovery measure, may prove to be detrimental (Higgins et al 2010).